Energy its production, conversion, and use in the service of man - Sporn, Philip (Oxford Pergamon Press, 1963)
Energy: Its Production, Conversion and Use in the Service of Man deals with energy production and conversion as well as its role in the advancement of civilization. Based on three lectures delivered in February-March 1962 under the auspices of the Graduate School of Business Columbia University, the book explores a wide range of energy-related issues such as energy supply, fossil fuels, electricity, nuclear power, coal, oil, and natural gas. This volume begins with a discussion of some of the current fallacies and overstatements about the role of energy, including the fear of a world shortage of energy, the premature optimism about the early replacement of fossil fuels by nuclear power, and the idea that energy is a panacea for the solution of the problems of underdeveloped countries. It argues that the future of energy in this century is secure owing to the large reserves of coal and the continuous discoveries of fresh sources of oil and natural gas, along with the ultimate promise of economic nuclear power. The importance of electricity in the economic growth of the United States is highlighted. Attention then turns to the probable consumption of energy in the United States in the years 1975 and 2000. The book concludes by calling for the continuous development of an adequate supply of fossil fuels. This book will be of interest to students, planners and policymakers, as well as workers and researchers in every phase of energy, including scientists, technologists, and engineers.--Provided by publisher.
Keywords: Power resources; Electronic books